A Normative Analysis of Juvenile Sentencing Laws in Indonesia: Reconciling Justice, Rehabilitation, and Victim Redress - Iskandarsyah Siregar; Aziz Rahimy (Britain International for Academic Research (BIAR-Publisher), 2023)
The issue of sentencing minors for criminal behavior persistently garners widespread public attention, stemming from the acknowledgement that children, too, can engage in illicit activities. Within the Indonesian context, juvenile punishment is formally governed by Act 11 of 2012, which outlines the Juvenile Criminal Justice System. This normative study aspires to scrutinize and answer two primary research questions, which are 1)To what extent does the existing stipulation in Act 11 of 2012, concerning the duration of incarceration for minors convicted of serious offenses, adhere to recognized principles of justice and accomplish the intended goals of the sentencing? and 2)What ideal legislative provisions should be adopted or revised pertaining to the length of incarceration for juveniles guilty of severe crimes in order to align with just principles and effectively fulfill the objectives of sentencing in future implementations? While the study maintains that the welfare and psychological well-being of children must be safeguarded against the adverse effects of detention, it simultaneously argues that equal consideration must be extended to the grievances and trauma experienced by the victims of juvenile crimes.